2023
DOI: 10.1002/jia2.26104
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 among adults living with HIV: correlates of mortality among public sector healthcare users in Western Cape, South Africa

Abstract: Introduction While a large proportion of people with HIV (PWH) have experienced SARS‐CoV‐2 infections, there is uncertainty about the role of HIV disease severity on COVID‐19 outcomes, especially in lower‐income settings. We studied the association of mortality with characteristics of HIV severity and management, and vaccination, among adult PWH. Methods We analysed observational cohort data on all PWH aged ≥15 years experiencing a diagnosed SARS‐CoV‐2 infection (until March 2022), who accessed public sector h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…For example, the results from a large American study using US National COVID Cohort Collaborative data showed that among PWH, individuals with a CD4 count lower than 200 cells/mm 3 had increased odds ratios (adjusted for demographics, lifestyle factors, and comorbidities) of 1.51, 2.73, and 3.1 for severe disease, hospitalization, and death, respectively. Similarly, Kassanjee et al reported a strong association between COVID-19-related mortality and suboptimal HIV control in a low-income, high-HIV-burden setting, even after adjusting for demographic characteristics, comorbidities, admission pressure, location, and time period [ 23 ]. In some studies, a low CD4 count (< 200 cells/mm 3 ) appeared to be a critical contributing factor to adverse COVID-19 outcomes, outweighing viral suppression as a significant contributor [ 20 , 25 ].…”
Section: Real World Data: Incidence Disease Severity and Mortality In...mentioning
confidence: 99%
“…For example, the results from a large American study using US National COVID Cohort Collaborative data showed that among PWH, individuals with a CD4 count lower than 200 cells/mm 3 had increased odds ratios (adjusted for demographics, lifestyle factors, and comorbidities) of 1.51, 2.73, and 3.1 for severe disease, hospitalization, and death, respectively. Similarly, Kassanjee et al reported a strong association between COVID-19-related mortality and suboptimal HIV control in a low-income, high-HIV-burden setting, even after adjusting for demographic characteristics, comorbidities, admission pressure, location, and time period [ 23 ]. In some studies, a low CD4 count (< 200 cells/mm 3 ) appeared to be a critical contributing factor to adverse COVID-19 outcomes, outweighing viral suppression as a significant contributor [ 20 , 25 ].…”
Section: Real World Data: Incidence Disease Severity and Mortality In...mentioning
confidence: 99%